Generation of a sexually mature individual of the Eastern dwarf tree frog, Litoria fallax, from cryopreserved testicular macerates: proof of capacity of cryopreserved sperm derived offspring to complete development. Issue 1 (15th August 2018) - Upton, Rose; Clulow, Simon; Mahony, Michael J; Clulow, John
Abstract : There are limited studies reporting the use of cryopreserved sperm in amphibians, and fewer reporting the generation of sexually mature individuals. This paper gives proof of concept to the value of genome banking for amphibian conservation by demonstrating in one amphibian species, the Eastern dwarf tree frog ( Litoria fallax ), that offspring produced from cryopreserved sperm are capable of achieving metamorphosis and reaching sexually maturity. Abstract: Amphibians are the most threatened vertebrate class globally based on recent rates of decline and extinction. Sperm cryopreservation and other assisted reproductive technologies have the potential to help manage small and threatened populations and prevent extinctions. There are a growing number of reports of recovery of amphibian sperm after cryopreservation, but relatively few published reports of amphibian embryos generated from frozen sperm developing beyond metamorphosis to the adult stage and achieving sexual maturation. In this study on the Eastern dwarf tree frog ( Litoria fallax ), a temperate amphibian species from eastern Australia, a small number of viable metamorphs and one sexually mature male frog (itself producing sperm) were produced from cryopreserved sperm, demonstrating the capacity of embryos generated from cryopreserved sperm to complete the life cycle to sexual maturity. Low progression rates between developmental stages were not deemed to be due to effects of cryopreservation, since control embryos from unfrozen sperm had a similarly low progression rate through development.